Implementasi Macro VBA Excel dalam Sistem Informasi Pelayanan Fasilitas Masjid Baitul Muttaqien Islamic Center Provinsi Kalimantan Timur - Tri Cahyono, Aris; Sudarlan, Sudarlan; Lily Anggraeni, Fauziah; Soetjipto, Rahmawati; Sari, Venny Nawang (Jurnal Sistem Informasi Akuntansi, 2024)
This research aims to find out how to design and create a Microsoft Excel Macro application in the Islamic Center employee rental information system. The object of this research is the Samarinda Islamic Center Mosque. Data collection techniques are field studies and library research. The analysis tool used is the Microsoft Excel Macro (VBA) program command. The research results show that this application can help input data, save data, edit data, Delete data, Cancel data input, and print reports as needed. So, it is hoped that this application can help the work process at the Samarinda Islamic Center Mosque